2016
DOI: 10.2147/dddt.s118768
|View full text |Cite
|
Sign up to set email alerts
|

Mimetics of brain-derived neurotrophic factor loops 1 and 4 are active in a model of ischemic stroke in rats

Abstract: BackgroundTwo dimeric dipeptides, bis-(N-monosuccinyl-l-seryl-l-lysine)hexamethylenediamide (GSB-106) and bis-(N-monosuccinyl-l-methionyl-l-serine) heptamethylenediamide (GSB-214), were designed based on the brain-derived neurotrophic factor (BDNF) loop 4 and loop 1 β-turn sequences, respectively. Earlier, both of these dipeptides were shown to exhibit neuroprotective activity in vitro (10−5–10−8 M). The present study aimed to investigate the mechanisms of action of these peptides and their neuroprotective act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 22 publications
2
25
0
5
Order By: Relevance
“…LM binding to TrkB lead to the activation of the TrkB-ERK1/2 pathway, similar to previous reports from in vitro studies that peptide mimetics of either loop I, III, or IV of BDNF can induce AKT and ERK phosphorylation ( 58, 59 ). TrkB activation also phosphorylates residue Y816 on its intracellular domain, which permits recruitment and activation of the PLCγ1 pathway, which activates numerous pathways including the Ca 2+ /calmodulin-dependent kinases ( 60, 61 ).…”
Section: Discussionsupporting
confidence: 90%
“…LM binding to TrkB lead to the activation of the TrkB-ERK1/2 pathway, similar to previous reports from in vitro studies that peptide mimetics of either loop I, III, or IV of BDNF can induce AKT and ERK phosphorylation ( 58, 59 ). TrkB activation also phosphorylates residue Y816 on its intracellular domain, which permits recruitment and activation of the PLCγ1 pathway, which activates numerous pathways including the Ca 2+ /calmodulin-dependent kinases ( 60, 61 ).…”
Section: Discussionsupporting
confidence: 90%
“…Based on the sequence of BDNF loop 4 and loop 1 β-turn, Gudasheva and colleagues have recently created two dimeric dipeptides, which mimic full-length BDNF. They exhibited varied abilities to activate the Akt and ERK pathways and exhibited therapeutic effects in the rat MCAO model [116].…”
Section: Improvement Of Bdnf Delivery and The Development Of New Trkbmentioning
confidence: 99%
“…We have developed low-molecular-weight compounds that mimic the beta-turns of some BDNF loops and experimentally proved that they selectively activate post-receptor cascades [12, 13]. In this case, BDNF mimetics selectively activating either PI3K/AKT or MAPK/ERK were found not to exhibit antidepressant activity, which indicates that both post-receptor signaling pathways are essential for this activity.…”
Section: Introductionmentioning
confidence: 99%
“…Western blot analysis revealed that GSB-106 activates BDNF-specific TrkB receptors and their post-receptor signaling pathways MAPK/ERK and PI3K/AKT [12, 16]. GSB-106 exhibited pronounced antidepressant activity in a rodent test battery at a dose of 0.1 to 1.0 mg/kg administered intraperitoneally [15, 17].…”
Section: Introductionmentioning
confidence: 99%